PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISTEM KEMUDI - Ahmad Nur Fitrotul Huda; Rabiman Rabiman (Universitas Sarjanawiyata Tamansiswa, 2016)
The objectives of this study were to describe (1) the use of jigsaw could improve learning activeness and (2) the use of jigsaw could improve learning achievement of steer system. This study was an action research. Data collection techniques used test and observation. Data analysis techniques used descriptive and quantitative analysis. This study shows that (1) the use of jigsaw could improve learning activeness. The learning activeness of cycle I was in low category, cycle II was in high category, and cycle III was in very high category. (2) The use of jigsaw could improve learning achievement of steer system. The improvement could be seen from the average score of pre cycle was 66.5, cycle I was 71.5, cycle II was 74.5, and cycle III was 89.5.